Um olhar sobre a formação continuada em teatro para professores das primeiras séries do ensino básico: acontecimento e experiência no projeto Conexão Galpão/ BH - Reginaldo dos Santos (2014)
It is necessary to value the symbolic access to a theater event (attending to a theater), either as an experience and as an access to a cultural asset, much higher than the value of the physical access so that it may change a subjects view of the theater. The Programa de Ações Formativas em Teatro (PAFT) - Program of Formative Attitudes in Theatre from the Projeto Conexão Galpão BH/MG Galpão Connection Program BH/MG aims to work in the field of symbolic and seeks to link the act of attending to the theater to mediation proposals with teachers of earlier grades of elementary school. This mediation considers the subjects emancipation and his/her personal experience as a proposal for teaching theater, opposing to the idea of passing along knowledge in the educational environment. The present research aimed to investigate how different kinds of knowledge approaching theater are organized by teachers of the lower grades of the elementary school, before and after attending the PAFT. Free word association tests were performed with four groups of teachers, whereas two of these groups were tested prior to participating in the PAFT and two after participation. Since the very beginning, videos and texts which had been stored by the Galpão Connection Program were also studied. As theoretical background we used the concept of emancipation, of event and experience, and also the Social Representation Theory. When interpreting the results, starting from the free word association test, we concluded that the word "culture" was presented as the Central Nucleus of representations for those teachers who had not participated in the PAFT and "Emotion" was the Central Nucleus of representations for those teachers who had participated. Through the content analysis, we also reached three categories: 1) Representations about the event (theater performance), 2) Representations about the theater as an educational tool and 3) Representations about the students experience. The results show that the significance of theater for the involved teachers, changed after the participation in the PAFT, considering that the teachers explanations, concepts, positions and statements value in a higher level the experience lived by the student at the theater, if compared to the outside view in associations previous to the participation in the PAFT.